Evaluation of bioactivities of Delonix regia extracts from different regions of Thailand - Suttijit Sriwatcharakul (My University, 2018)
This research is to study bioactivity of Delonix regia flower and leaf extracts collected in Thailand. We analyzed for efficacy of free radical scavenging and found that flower and leaf extracts from Samut Prakan showed the strongest percentage of reduction with IC50 50.21 and 105.0 mg/ml, respectively. The result of evaluated phytochemicals revealed that Chon Buri's flower extract had the highest of total phenolic and tannin contents at 200 mg GAE/g extract and 32 mg TAE/g extract, respectively. Furthermore, Samut Prakan's flower extract had the highest flavonoid compounds at 328.5 mg QE/g extract. To examine cytotoxicity on breast cancer cell lines, we found that Samut Prakan's flower extract had the most cytotoxicity CC50 value, 5000 µg/ml. In conclusion, we found that the flower of Delonix regia is the promising part for the further study because the antioxidant activity and cytotoxicity strongly enhances when flower extract concentration is increased.
Keywords: Tannin; Phytochemistry and Biological Activities